Beyond the depth of narratives, does the multi-layer monitoring-driven view matter in disclosure? Evidence from MENA countries - Maysa Ali M. Abdallah (Cogent Business & Management, 2023)
This study goes beyond firm-specific characteristics to assess the role of multi-layer monitoring mechanisms on narrative disclosure in the Middle East and North Africa (MENA) regions. By using a neo-institutional perspective and analyzing data from 154 non-financial firms between 2015 and 2018, this study reveals that the depth of narratives in MENA countries falls short of expectations after the global reporting initiative guidance. In addition, both firm and national monitoring mechanisms put enormous pressure on management to increase the content of narrative reports. The firm monitoring mechanisms presented in board independence, gender diversity, and institutional ownership enhance the richness of narrative sections. Considering the rule of law and regulations quality, the results reveal that the uniqueness of the MENA national mechanisms affects the firm-level characteristics, which causes regional differences among MENA firms. Furthermore, the quality of national monitoring mechanisms moderates the effect of institutional ownership on the depth of the narrative information, since firms owned by institutional investors and operating in highly regulated countries are more likely to display deeper narratives. This study provides significant evidence regarding the effects of both firm and national monitoring mechanisms on the depth of narratives, drawing on evidence from international companies with diverse boards in terms of independence and gender and operating in highly regulated countries. This work offers unique insights from the neo-institutional theory, which asserts that firms adopt social norms and rules into their operations and structures to gain social acceptance and legitimacy.
Keywords: 650; depth of narratives; institutional ownership; multi-layer monitoring mechanisms; Neo-institutional theory; regulatory quality; rule of law quality